IMPLEMENTATION OF NURSING CARE BY NURSES IN THE PSYCHOLOGICAL, SOCIAL, AND SPIRITUAL ASPECTS OF INPATIENTS IN THE INTENSIVE CARE UNIT - Nugrahaeni Firdausi; Widhi Sumirat (Suluh Adiluhung Publisher (SAPub), 2026)
Nursing care is a series of professional activities provided directly to clients with a holistic approach that encompasses physiological, psychological, social, and spiritual aspects. This approach is especially important for inpatients in the Intensive Care Unit, as disruptions in one dimension can affect other dimensions. This study aims to analyze the implementation of nursing care by nurses on the psychological, social, and spiritual aspects of inpatients in the Intensive Care Unit of Kediri Regency Hospital. This study used a quantitative method with a descriptive design. The sampling technique used was total sampling with respondents from all nurses in the Intensive Care Unit. Data collection was conducted through structured interviews using questionnaires in November–December 2024. Data analysis was conducted univariately and presented in the form of frequencies and percentages. The results showed that the implementation of nursing care in the psychological aspect was in the good category (100%). In the spiritual aspect, the implementation was in the good category at 42%, sufficient at 52%, and lacking at 6%. Meanwhile, the implementation of nursing care in the social aspect showed a good category at 84%, sufficient at 13%, and lacking at 3%. The conclusion of this study shows that the implementation of nursing care by nurses in the Intensive Care Unit has been running well in the psychological and social aspects, but still needs improvement in the spiritual aspect to realize holistic and quality nursing care.